COMMUNITY SERVICE AT SUTERU FARM, TEGAL WARU VILLAGE, CIAMPEA DISTRICT, BOGOR REGENCY - Retno Martanti Endah Lestari; Hasrul Hasrul; Lilis Khotijah (Research Collaboration Community (RCC), 2023)
Suteru Farm is a Holland fries (FH) dairy farm that was established in 2013, with 32 biological assets and a farm area of 11,000m2. The location of this farm is in the vicinity of the community housing of Tegal Waru Village, Ciampea District, Bogor Regency, where the average layout of the residences is still far from one another so that they still have vacant land to plant productive plants. Our goal in conducting community service activities at Suteru Farm is to help form a community forum for producing feed crops around the farm, optimizing vacant land to become productive for plant feed by providing knowledge and skills for the community in cultivating feed crops, providing knowledge and skills in making fermentation green plants from cultivation to marketing, providing skills in livestock financial management. Efforts made for Suteru Farm and other farms in the Tegal Waru Village area need to offer several solutions including: 1) Optimization of vacant land around the community's residential yards by cultivating forage in the form of grass and legumes; 2) Application of preservation technology including fermentation; 3) Centralized management in one container for the management of fermented cattle feed so that it goes directly to the hands of the farm; and 4) improve the financial management of livestock in order to increase profitability. The target that we set for this activity is to run within 8 (eight) months, through the field survey method of potential vacant land, Forum Group Discussion (FGD) with Suteru Farm management and representatives of the local community by discussing knowledge about forage crop cultivation, forage grass fermentation and marketing. , lectures and trainings, practices from the solutions offered to mentoring.